The Treasury Single Account (TSA) Policy In The Nigerian Public Sector: The Qualitative Analysis - Babatope, Taiwo Isaac (2023)
This research is about implementation of the Treasury Single Account (TSA) policy in the Nigerian public sector. The TSA policy was implemented in the year 2015 through Presidential order, directing all Nigerian public sector to adopt TSA policy, and thus, government’s bank accounts were consolidated. The TSA policy is under the supervision of federation Accountant-General, being the treasury officer. This research specifically used Ekiti State as case study to explore in-depth information regarding the likely pressures, possible conflict of interests among stakeholders in the TSA policy, and to explore the process of accountability that government put in place for implementation of the TSA policy. Further area of the study explored the impact of TSA on public sector financial performance. The research used institutional theory and legitimacy theory, the institutional theory was used to explore the type of pressures which are coercive, mimetic, and normative isomorphism and legitimacy theory to justify the legitimacy of the TSA policy. Qualitative methodology was used, data were collected through semi structured interviews conducted with experienced senior officers who were in-charge of the treasury and the TSA policy in Ekiti State. Data was also gathered through financial documents such as Audited Financial Statement of Ekiti State, Cash Management Manual, Financial Regulation, and the Central Bank of Nigeria (CBN) guidelines for the TSA policy.